Rural development in Romania: Evolutions and disparities at regional level - Sorinel Ionel Bucur (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Rural development was and continues to be considered an essential imperative, being one of the reasons for which the concept of sustainable development and diversification in the rural space has registered a high emergence frequency and debates in the specialty literature. The sustainable and complex development of the rural space means the implementation of some measures which should meet the need to eliminate the whole range of drawbacks of agriculture, respectively the gaps present between the different areals. In this context, on basis of public information using the well known statistical methods, the present approach wishes to realize a comparative inter-regional analysis from the demo - economic and social perspective of the Romanian rural space.
Keywords: R11; R12; 330; rural development; disparities; regional dimension